Public policies and silvo-pastoral systems in Latin America: A comparative study - Moreno Lerma, Leonardo; Díaz, Manuel F.; Burkart, Stefan (Bioversity International and the International Center for Tropical Agriculture, 2021)
The global projections of population and food demand increases by 2050 highlight the importance of Latin America as one of the future big food suppliers for our planet. The region has high agricultural potential and activities such as cattle farming can increase the global food supply, i.e. through the adoption of sustainable technologies such as silvo-pastoral systems. Despite the importance of this economic sector for the region, its negative environmental impacts (especially those of traditional extensive production systems) are numerous and the shift towards sustainability is perceived as slow and uncoordinated. This study aims at identifying both success stories and difficulties in the implementation of public policies for the development of sustainable cattle production systems in Colombia, Argentina and Costa Rica during the period 2010-2020. Based on literature review, media analysis and legal document reviews, a qualitative descriptive analysis was carried out, documenting and outlining the main political activities in the region. The results highlight the development and application of policies aimed at the use of sustainable production technologies, the adaptation of pastures to changing environmental conditions and the use of silvo-pastoral systems for cattle production. Although common successes are identified in the three countries, such as the existence of a large number of public policies aimed at promoting sustainable livestock - which is strengthened through e.g. national level development plans and legislative advances - they also coincide in difficulties, such as a minimal articulation between national and local policies and the lack of continuity of development programs. We conclude that, although the selected countries have different socioeconomic characteristics, as well as different levels of progress in the implementation of their policies, the general perception among the three countries is relatively similar to the extent that their efforts are still insufficient, i.e. when the commitments made during the COP21 are being considered. Although the advances made so far provide valuable contributions, it is necessary to treat them as a first stage in a long-range process towards sustainability, and support their continuity and further out-scaling, i.e. for reaching the ultimate goal of a broader adoption of silvo-pastoral systems.